Metabolic bulk volume predicts survival in a homogeneous cohort of stage II/III diffuse large B-cell lymphoma patients undergoing R-CHOP treatment - Jin, Hyun; Jin, Myung; Lim, Chae Hong; Choi, Joon Young; Kim, Seok-Jin; Lee, Kyung-Han (Frontiers in Oncology, 2023)
Purpose: Accurate risk stratification can improve lymphoma management, but current volumetric FDG indicators require time-consuming segmentation of all lesions in the body. Herein, we investigated the prognostic values of metabolic bulk volume (MBV) and bulky lesion glycolysis (BLG). Methods: Study subjects were a homogeneous cohort of 242 stage II/ III DLBCL patients who underwent first-line R-CHOP treatment. Baseline PET/CT was analyzed for maximum transverse diameter (MTD), total metabolic tumor volume (TMTV), total lesion glycolysis (TLG), MBV, and BLG. Volumes were drawn using 30% SUVmax as threshold. Kaplan-Meier and Cox proportional hazards analysis assessed prediction of overall survival (OS) and progression-free survival (PFS). Results: During a median follow-up period of 5.4 y, events occurred in 85 patients, including progression, relapse, and 65 deaths. ROC analysis identified an optimal TMTV of 112 cm3, MBV 88 cm3, TLG 950, and BLG 750 for events. Patients with high MBV more likely had stage III disease, worse ECOG, higher IPI risk, LDH, SUVmax, MTD, TMTV, TLG, and BLG. Kaplan-Meier analysis showed that high TMTV (P = 0.005 and < 0.001), MBV (both P < 0.001), TLG (P < 0.001 and 0.008), and BLG (P = 0.018 and 0.049) were associated with significantly worse OS and PFS. On multivariate analysis, older age (> 60 y; HR, 2.74; 95% CI, 1.58-4.75; P < 0.001) and high MBV (HR, 2.74; 95% CI, 1.05-6.54; P = 0.023) were independent predictors of worse OS. Older age (HR, 2.90; 95% CI, 1.74-4.82; P < 0.001) and high MBV (HR, 2.36; 95% CI, 1.08-5.16; P = 0.032) were independent predictors of worse PFS. Among subjects ≤ 60 y, high MBV remained the only significant independent predictor of worse OS (HR, 4.269; 95% CI, 1.03-17.76; P = 0.046) and PSF (HR, 6.047; 95% CI, 1.73-21.11; P = 0.005). Among stage III disease, only greater age (HR, 2.540; 95% CI, 1.22-5.30; P = 0.013) and high MBV (HR, 6.476; 95% CI, 1.20-31.9; P = 0.030) were significantly associated with worse OS. Conclusions: MBV easily obtained from the single largest lesion may provide a clinically useful FDG volumetric prognostic indicator in stage II/III DLBCL patients.